Aplikasi Chatbot sebagai Layanan Informasi Virtual pada Website Infinite Learning - Syarof, Hugo Irfenz; Rasal, Isram (Jurnal Pendidikan Informatika (EDUMATIC), 2024)
This research focuses on the development and implementation of virtual information services in the form of an artificial intelligence (AI) based chatbot on the Infinite Learning website. The primary goal of this study is to develop a chatbot application as a virtual information service to improve the quality and effectiveness of digital learning. The method used is Research and Development to develop the product and test its effectiveness, with the System Development Life Cycle (SDLC) model including stages of needs analysis, system design, system creation, and implementation as well as testing. This chatbot was designed and built with the help of IBM applications, namely Watson Assistant and Smart Document Understanding. Testing in this study used Black box testing to detect problems in the system. Data was collected through surveys, questionnaires, and interviews with users, and analysed to evaluate the chatbot's performance. Our findings are a virtual information service on the Infinite Learning website using a chatbot integrated with IBM application technology. The test results show the system runs well with an acceptable score of 83%.